2022
DOI: 10.1016/j.cub.2021.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Mechano-transduction via the pectin-FERONIA complex activates ROP6 GTPase signaling in Arabidopsis pavement cell morphogenesis

Abstract: During growth and morphogenesis, plant cells respond to mechanical stresses resulting from spatiotemporal changes in the cell wall that bear high internal turgor pressure. Microtubule (MT) arrays are reorganized to align in the direction of maximal tensile stress, presumably reinforcing the local cell wall by guiding the synthesis of cellulose. However, how mechanical forces regulate MT reorganization remains largely unknown. Here, we demonstrate that mechanical signaling that is based on the Catharanthus rose… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 71 publications
3
85
0
Order By: Relevance
“…19,61 Finally, pectin binding to FER and other CrRLK1Ls appears to provide an important mechanism for Article sensing mechanical stress to feedback regulate cell growth, morphogenesis, and cell wall integrity maintenance in plants. 46,62 Therefore, the pectin-FER-ROP system may provide a paradigm for our understanding of how plant cells monitor the cell wall status and mechanical stresses to feedback regulate a plethora of important processes, such as cell expansion, cell shape formation, cell wall integrity maintenance, and stress responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,61 Finally, pectin binding to FER and other CrRLK1Ls appears to provide an important mechanism for Article sensing mechanical stress to feedback regulate cell growth, morphogenesis, and cell wall integrity maintenance in plants. 46,62 Therefore, the pectin-FER-ROP system may provide a paradigm for our understanding of how plant cells monitor the cell wall status and mechanical stresses to feedback regulate a plethora of important processes, such as cell expansion, cell shape formation, cell wall integrity maintenance, and stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing studies show that FER, and other CrRLK1L family members, also participate in sensing and/or transducing the mechanical signals of either internal or external origin via their linkage with the structural cell wall components, such as pectin in Arabidopsis. 36,46,47,56,62 Coupling the sensing and signaling of extracellular matrices with mechanical sensing and signaling by a cell surface receptor is also common in animals and fungi. 67,68 In short, our findings here, together with recent studies showing CrRLK1Ls in RALF perception and their involvement in mechanical sensing and signaling, 35,36,45,47,56,63 suggest that FER and its relatives act as integrators of external signals.…”
Section: Discussionmentioning
confidence: 99%
“…Roots can show responses to touch or impermeable mechanical barriers by changes in cell division patterns, growth direction, cell differentiation and gene expression. Changes in pressure at the plant cell surface are signalled by mechanosensitive ion channels and kinases to the microtubule cytoskeleton, and lead to altered cytoskeletal architecture and reinforcement of the cell wall (Hamilton et al 2015;Tang et al 2021). Dupuy et al (2018) recently suggested re-visiting micromechanics of rooting development in soil by considering recent advances in granular matter physics.…”
Section: Arbuscular Mycorrhiza (Am) Formationmentioning
confidence: 99%
“…It has been reported that inhibition of ARF-GEF function can lead to reduced internalisation of PM-localised proteins through inhibition of endocytosis (Irani et al, 2012;Naramoto et al, 2010;Teh and Moore, 2007). We therefore hypothesised that secRFP:RLP4sΔECD undergo constitutive secretion, but are rapidly endocytosed under standard growth conditions and therefore do not accumulate at detectable levels at the PM The extracellular domain of RLP4s contains an MLD, a domain which is also found in RLKs of the CrRLK-L1 family, where it has been shown to bind pectins in vivo (Lin et al, 2022;Tang et al, 2022). To test whether RLP4s can also associate with the cell wall via their ECD, we expressed RLP4s variants that comprised solely of their ECD fused to RFP, while lacking their intracellular and transmembrane domains (pUBQ10::RLP4s-ECD:RFP).…”
Section: Establishment Of Rlp4s Cell Edge Polarity Requires Rab-a5c A...mentioning
confidence: 99%